Application of a novel friction stir spot welding process on dissimilar aluminum joints. (October 2018) - Ibrahim, Isam Jabbar; Yapici, Guney Guven
Abstract: Intermediate layer friction stir spot welding (IL-FSSW) is introduced in this study as a novel spot welding technique to eliminate the keyhole associated with the conventional friction stir spot welding (FSSW). This process is utilized for fabricating a joint of 6061-T6 and 2024-T3 aluminum alloys. The welding process is based on preventing the keyhole occurrence owing to the addition of an intermediate layer (IL), rendering additional post-treatments unnecessary. Results indicated a decent joint appearance without a keyhole along with improved mechanical performance yielding a lap shear force over 4.5 kN. The microstructure of the weld cross-section indicated that the IL contributed to the nugget zone and revealed its influence on the formation of a hooked structure. The fracture surface showed ductile features within the IL boundary, whereas mixed failure was prevalent outside it.